The role of diet therapy in insulin resistance in women with polycystic ovary syndrome - H.B. Semenyna; T.V. Fartushok; N.V. Fartushok; N.Ya. Dumanchuk; O.M. Yurchyshyn (Medičnì Perspektivi, 2025)
The purpose of the study is to substantiate, based on a review of literary sources, the effectiveness of various types of diet therapy as an initial method of treatment in women with polycystic ovary syndrome and insulin resistance, their effect on the normalization of the menstrual cycle, correction of metabolic disorders and reduction of the level of insulin resistance. From 2018 to 2024 40 articles were analyzed with key words: polycystic ovary syndrome (PCOS), insulin resistance, diet therapy, Mediterranean diet, ketogenic diet, low-carbohydrate diet, low-fat diet, Homeostasis model assessment (HOMA) according to which a review of the available literature was conducted in PubMed, National Library of Medicine, Medscape. The study did not include pregnant, lactating women who took hormonal therapy and/or insulin sensitizers during the last 2 months, had liver, kidney, and heart diseases that failed local treatment of hirsutism, with congenital hyperplasia of the adrenal glands, androgen-secreting tumors, Cushing's syndrome. A review and analysis of studies on the effects of a ketogenic diet for 12 weeks, in which 14 overweight women with a diagnosis of polycystic ovary syndrome, participated. 40 articles were studied using bibliographic and analytical methods. At the beginning of the study patients had HOMA-IR above 2.5, which confirms insulin resistance. After using ketogenic diet, a significant decrease in the level of glucose, insulin, and, therefore, the HOMA index was observed. There were significant changes in lipid profiles with a decrease in triglycerides, total cholesterol, and low-density lipoproteins along with increases in high-density lipoprotein. Anthropometric measurements revealed a weight loss of 8.78 kg and a significant decrease in the body mass index of 3.18. A study of 72 women with PCOS showed a superior efficacy of a Mediterranean diet (MED) combined with a low-carbohydrate (LC) diet versus a low-fat diet alone. In patients who used the combination of MED/LC diet, in 86.7% of cases, the regular menstrual cycle was restored, and pregnancy occurred.